Guía etnobotánica de las plantas más comúnmente usadas en la parroquia de Canchagua, cantón Saquisilí, Cotopaxi. - Gavilanes, Lizeth (2020)
The parish of Canchagua is one of the three rural parishes of the Saquisili canton, Cotopaxi province; After analyzing literatures of ethnobotany within the Saquisilí canton, it is affirmed that there are no ethnobotanical or plant related projects within it, for this reason the present research study of an ethnobotanical guide to the most commonly used plants within the parish of Canchagua, canton Saquisili, Cotopaxi, intended to promote the use of plants and the conservation of intangible use (ancestral knowledge). For this purpose, the following objectives were determined: make a situational diagnosis of the study area, through the compilation of primary and secondary bibliography on useful plants with more uses for community members; Inventory useful plants for the development of a key to identify botanical species used in the parish of Canchagua and synthesize the information obtained through the design of an ethnobotanical guide as a means of information for future research and potential uses in tourism, All this was based on the methodology of field trips, interviews, botanical collection and the synthesis of information on botanical files in order to know the use of each of the plants and their dosage. As a result of the investigation, 21 species of plants were identified, of which 19 medicinal uses, 11 food uses, 1 textile use and an ornamental plant were identified, which are divided into 12 families, the family with the highest number of species was Asteracea, and the preparation methods found were: infusion, scalding, maceration, footbath and gargle. The botanical samples will be deposited in the Herbarium of the UTCEC, Canchawasi Museum, Catholic University of Ecuador and a foreign entity. The authorities of the Decentralized Autonomous Government of the rural parish of Canchagua and the interviewed inhabitants of the different communities agree with the research, since through it an ethnobotanical guide will be carried out that will benefit the parish to promote knowledge about the uses of the plants and their importance in turn will serve as a tool for national and foreign tourists visiting the natural and cultural resources of the parish.